Knowledge, attitudes, and practices on the prevention of intestinal Schistosomiasis in rural areas of Kimpese, Democratic Republic of the Congo - Munenge, Anderson M.; Bomoi, Henry-Jacques M.; Masikini, Fiston B.; Kanku, Becker T.; Mabubu, Prescillia P.; Okito, Dénise W.; Amogu, Jean-Jacques D.; Kabena, Odette N.; Tangou, Thierry T. (Orapuh Journal, 2025)
IntroductionSchistosomiasis remains widespread in sub-Saharan Africa, particularly in the Central Congo Province of the Democratic Republic of the Congo (DRC), where it is endemic.PurposeThis study aimed to assess the knowledge, attitudes, and practices (KAP) of the rural population of Kimpese regarding the prevention of intestinal schistosomiasis.MethodsA random sampling technique was employed, using semi-structured and informal interviews to collect data.ResultsThe findings revealed that while 96% of respondents were aware of schistosomiasis, only 41% had knowledge of or practised preventive measures.ConclusionThese findings underscore the need to enhance health education and water sanitation initiatives to address this public health challenge.